Electronic Medical Records in Greece and Oman: A Professional’s Evaluation of Structure and Value - Xanthidou, Ourania Koutzampasopoulou; Shuib, Liyana; Xanthidis, Dimitrios; Nicholas, David (MDPI, 2018)
An Electronic Medical Record (EMR) is a patient’s database record that can be transmitted securely. There are a diversity of EMR systems for different medical units to choose from. The structure and value of these systems is the focus of this qualitative study, from a medical professional’s standpoint, as well as its economic value and whether it should be shared between health organizations. The study took place in the natural setting of the medical units’ environments. A purposive sample of 40 professionals in Greece and Oman, was interviewed. The study suggests that: (1) The demographics of the EMR should be divided in categories, not all of them accessible and/or visible by all; (2) The EMR system should follow an open architecture so that more categories and subcategories can be added as needed and following a possible business plan (ERD is suggested); (3) The EMR should be implemented gradually bearing in mind both medical and financial concerns; (4) Sharing should be a patient’s decision as the owner of the record. Reaching a certain level of maturity of its implementation and utilization, it is useful to seek the professionals’ assessment on the structure and value of such a system.